Prolonged argatroban clearance in a critically ill patient with heparin-induced thrombocytopaenia. Issue 4 (6th April 2017) - Tee, Caroline; Yuen, Yi Ching; Lim, Cheryl; Yap, Eng Soo
Abstract : This is a case of argatroban use in a critically ill patient with heparin-induced thrombocytopaenia (HIT), presenting with unexpectedly prolonged drug clearance possibly secondary to hepatic congestion due to reduced cardiac contractility. A 63-year-old woman from Asia with end-stage renal failure was hospitalised in the critical care unit with non-ST elevation myocardial infarction with underlying triple vessel disease. She was subsequently started on intravenous unfractionated heparin infusion after an intra-aortic balloon pump was inserted. Six days after the initiation of heparin, she developed HIT and argatroban was started for treatment of HIT. Despite starting on the recommended dose of 2µg/kg/min, she developed significantly prolonged activated partial thromboplastin time (aPTT) with delayed clearance. Argatroban was stopped 14 hours after time of initiation in view of the markedly prolonged aPTT (in the range of 145 s), and levels only normalised at approximately 60 hours after argatroban was stopped.